Effects of a telehealth-supported home-based exercise program on functional capacity, sarcopenia risk, and patient-reported outcomes in non-dialysis stage 4–5 chronic kidney disease - Büşra Yıldırım Uz; Gökçe Yağmur Güneş Gencer; Feyza Bora (Journal of Nephrology, 2026)
Abstract Background Evidence on the effects of 12-week telehealth-supported home-based exercise in advanced non-dialysis chronic kidney disease (CKD) remains limited. This study evaluated its effects on functional capacity, sarcopenia risk, and patient-reported outcomes in patients with stage 4–5 CKD. Methods In this prospective, parallel-group randomized controlled trial (October 2024–July 2025), 54 non-dialysis patients aged ≥45 years with stage 4–5 CKD were randomized 1:1 to a 12-week telehealth-supported home-based exercise program plus usual nephrology care or usual care alone. Complete-case analyses included 51 participants (exercise group: n = 25 [stage 4, n = 21; stage 5, n = 4]; control group: n = 26 [stage 4, n = 20; stage 5, n = 6]). The primary outcome was change in 6-minute walk test distance. Secondary outcomes included physical performance, sarcopenia risk, fatigue, mood symptoms, sleep quality, and health-related quality of life. Results Fifty-one participants completed the study (exercise group, n = 25; control group, n = 26). Compared with controls, the exercise group showed a greater improvement in 6-minute walk test distance (+29.41 ± 35.63 m vs −19.27 ± 33.62 m; P < .001), which remained significant after covariate adjustment. Significant improvements were also observed in sarcopenia risk, fatigue, mood symptoms, sleep quality, physical performance, and quality of life. Among intervention participants, 40% used the web-based platform and 60% received video-based support. Conclusions A 12-week telehealth-supported home-based exercise program significantly improved functional capacity and multiple patient-reported outcomes in patients with non-dialysis stage 4–5 CKD.